Role of 3D SPACE sequence and susceptibility weighted imaging in the evaluation of hydrocephalus and treatment-oriented refined classification of hydrocephalus - Amarnath Chellathurai; Komalavalli Subbiah; Barakath Nisha Abdul Ajis; Suhasini Balasubramaniam; Sathyan Gnanasigamani (Indian Journal of Radiology and Imaging, 2018)
Objective: The aim of our study was to evaluate the diagnostic utility of three-dimensional sampling perfection with application optimized contrast using different flip angle evolution (3D SPACE) sequence and Susceptibility Weighted Imaging (SWI) in hydrocephalus and to propose a refined definition and classification of hydrocephalus with relevance to the selection of treatment option. Materials and Methods: A prospective study of 109 patients with hydrocephalus was performed with magnetic resonance imaging (MRI) brain using standardized institutional sequences along with additional sequences 3D SPACE and SWI. The images were independently read by two senior neuroradiologists and the etiopathogenesis of hydrocephalus was arrived by consensus. Results: With conventional sequences, 46 out of 109 patients of hydrocephalus were diagnosed as obstructive of which 21 patients showed direct signs of obstruction and 25 showed indirect signs. In the remaining 63 patients of communicating hydrocephalus, cause could not be found out in 41 patients. Whereas with 3D SPACE sequence, 88 patients were diagnosed as obstructive hydrocephalus in which all of them showed direct signs of obstruction and 21 patients were diagnosed as communicating hydrocephalus. By including SWI, we found out hemorrhage causing intraventricular obstruction in three patients and hemorrhage at various sites in 24 other patients. With these findings, we have classified the hydrocephalus into communicating and noncommunicating, with latter divided into intraventricular and extraventricular obstruction, which is very well pertaining to the selection of surgical option. Conclusion: We strongly suggest to include 3D SPACE and SWI sequences in the set of routine MRI sequences, as they are powerful diagnostic tools and offer complementary information regarding the precise evaluation of the etiopathogenesis of hydrocephalus and have an effective impact in selecting the mode of management.